Further data on sentinel lymph node mapping in vulvar cancer by blue dye and radiocolloid Tc99. Issue 1 (1st January 2007) - Rob, Lukas; Robova, Helena; Pluta, Marek; Strnad, Pavel; Kacirek, Josef; Skapa, Petr; Taborska, Katerina
Abstract : We studied the distribution of sentinel lymph nodes (SLNs) in vulvar cancer using blue dye and 99m Tc radiocolloid and evaluated the techniques used, including the optimum timing of preoperative scintigraphy scans and its contribution to 99m Tc SLN detection over that of the intraoperative handheld gamma probe. Fifty-nine women with squamous cell cancers <4 cm treated at our institution between December 2001 and December 2005 were included in this study. Blue dye alone was used in the first 16 women (group A) and the combination of 99m Tc and blue dye was used on 43 women (group B). Of the 118 SLN detected in 82 groins, 83.9% (99) were sited in the superficial medial and intermediate inguinal chain, none were in superficial lateral groin, 16.1% (19) were deep femoral. The patient-specific SLN detection and false-negative rate in group B was 100% and 0%, compared to 68.8% (11/16 cases) and 6.3% (1/16) in group A. The optimum timing for preoperative lymphoscintigraphy scans was 45 min postinjection, but intraoperative use of the handheld gamma probe yielded 15% more "hot" nodes and allowed tailored placement of the lymphadenectomy incision. Eighty-four percent of SLNs were in the medial and intermediate region of the superficial inguinal chain, 16.1% were deep femoral. The combined use of 99m Tc radiocolloid and blue dye was significantly superior at SLN detection than blue dye alone. 99m Tc SLN detection using the intraoperative handheld probes was not enhanced by preoperative scintigraphy scans.